When Less Is More: Why Limited Entrepreneurship Education May Result in Better Entrepreneurial Outcomes - Niklas Elert; Karolin Sjöö; Karl Wennberg (Research Institute of Industrial Economics (IFN), 2020)
Entrepreneurship research suggests that entrepreneurship education and training can bridge the gender gap in entrepreneurship, but little empirical research exists assessing the validity and impact of such initiatives. We examine a large government-sponsored entrepreneurship education program aimed at university students in Sweden. While a pre-study indicates that longer university courses are associated with short-term outcomes such as increased self-efficacy and entrepreneurial intentions, results from a more comprehensive study using a pre-post design suggest little effect from these extensive courses on long-term outcomes such as new venture creation and entrepreneurial income. In contrast, we do find positive effects on these long-term outcomes from more limited but more specific training interventions, especially for women. Our study suggests that less extensive but more tailored interventions can be more beneficial than longer or more extensive interventions in promoting entrepreneurship in general, and entrepreneurship of underrepresented groups in particular. We discuss implications for theory, education, and policy.
Keywords: D22; L25; L26; 330; Entrepreneurship; Entrepreneurship education; Performance